Large pseudoaneurysm following right ventricle to pulmonary artery homograft placement in an infant - Rini Sahewalla; Robert D Ross; Ralph E Delius; Ryan Halas; Premchand Anne (Wolters Kluwer Medknow Publications, 2018)
Pseudoaneurysm (PSA) is a known but rare complication of the right ventricle to pulmonary artery (RV-PA) conduits. The patient's clinical presentation can be variable ranging from asymptomatic to potential rupture. We describe an unusual case of a massive PSA in an infant who underwent RV-PA pulmonary homograft placement after relief of right ventricular outflow tract obstruction.